An epidemiology report for primary central nervous system tumors in adolescents and young adults: a nationwide population-based study in France, 2008–2013. Issue 6 (4th December 2019) - Ng, Sam; Zouaoui, Sonia; Bessaoud, Faiza; Rigau, Valérie; Roux, Alexandre; Darlix, Amélie; Bauchet, Fabienne; Mathieu-Daudé, Hélène; Trétarre, Brigitte; Figarella-Branger, Dominique; Pallud, Johan; Frappaz, Didier; et al.
Abstract: Background: Primary central nervous system tumors (PCNST) among adolescents and young adults (AYA, 15–39 y) have rarely been reported. We present a nationwide report of PCNST histologically confirmed in the French AYA population between 2008 and 2013. Methods: Patients were identified through the French Brain Tumor Database (FBTDB), a national dataset that includes prospectively all histologically confirmed cases of PCNST in France. Patients aged 15 to 39 years with histologically confirmed PCNST diagnosed between 2008 and 2013 were included. For each of the 143 histological subtypes of PCNST, crude rates, sex, surgery, and age distribution were provided. To enable international comparisons, age-standardized incidence rates were adjusted to the world-standard, European, and USA populations. Results: For 6 years, 9661 PCNST (males/females: 4701/4960) were histologically confirmed in the French AYA population. The overall crude rate was 8.15 per 100 000 person-years. Overall, age-standardized incidence rates were (per 100 000 person-years, population of reference: world/Europe/USA): 7.64/8.07/8.21, respectively. Among patients aged 15–24 years, the crude rate was 5.13 per 100 000. Among patients aged 25–39 years, the crude rate was 10.10 per 100 000. Age-standardized incidence rates were reported for each of the 143 histological subtypes. Moreover, for each histological subtype, data were detailed by sex, age, type of surgery (surgical resection or biopsy), and cryopreserved samples. Conclusion: These data represent an exhaustive report of all histologically confirmed cases of PCNST with their frequency and distribution in the French AYA population in 2008–2013. For the first time in this age group, complete histological subtypes and rare tumor identification are detailed.